Immune response to BNT162b2 SARS-CoV-2 vaccine in patients living with HIV: The COVIH-DAPT study - Manni, Sabrina; Ruetsch, Caroline; Fabre, Roxane; Ticchioni, Michel; Graça, Daisy; Pradier, Christian; Seitz-Polski, Barbara; Lotte, Laurene; Brglez, Vesna; Vassallo, Matteo (Frontiers in Immunology, 2023)
Introduction: Data on immune response to SARS-CoV-2 vaccine in patients living with HIV (PLWH) over a period longer than 3 months are currently limited. We measured the immune response after BNT162b2 vaccination against SARS-CoV-2 in this population. Methods: We prospectively enrolled PLWH on successful antiretroviral therapy, initiating vaccination with two doses of the BNT162b2 SARS-CoV-2 vaccine administered at six-week interval. SARS-CoV-2 humoral and cellular responses and lymphocyte cell subsets were recorded at inclusion and 6 weeks (W6), 3 months (M3) and 6 months (M6) later. Humoral, humoral strong and cellular responders were defined by IgG titers >10, >264 BAU/mL and IFN-γ T cell release, respectively. Results: Nineteen subjects without SARS-CoV-2 infection were included (74% men, mean age 51 years, CD4 nadir 399/mm3). All subjects were humoral responders, their antibody titer peak reached at M3. Strong responders’ rates were 63% and 21% at M3 and M6, respectively. CD19+CD10+ B cells had increased significantly at W6 then decreased at M3, while CD19+CD27+ B cells remained unchanged. Rates of patients with a cellular response increased from 39% at W6 to 69% at M6. Cellular responders had significantly higher CD3+, CD4+ and CD8+ Effector Memory cells at inclusion (p=0.048, p=0.024, p=0.012, respectively) and CD4+ Terminally Differentiated Effector Memory cells at M3 (p=0.044). Discussion: PLWH have a robust immune response after SARS-CoV-2 vaccination, but a rapid decline in humoral response from 3 months onwards, due to a blunted memory B cell response. Analysis of lymphocyte subsets may help identify optimal times for vaccine boosters.